EFFECTIVE ALGORITHM FOR STRUCTURAL OPTIMIZATION SUBJECTED TO FATIGUE DAMAGE AND RANDOM EXCITATION - Milan SÁGA; Milan VAŠKO; Zuzana SÁGOVÁ; Marian HANDRIK (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of the paper is to present the computationally timeconsuming task of simulating the process of randomly oscillating thin-shell structures to realize an optimal design with limitations in terms of fatigue damage. The most important aim here is to design an effective optimization algorithm and choose an appropriate approach for the evaluation of multiaxial fatigue damage in the context of the random and non-proportional character of stress in the structure when considering the standard finite element model. The authors propose their own optimization algorithm, which is described in the present study and, on the basis of tests, has proven to be suitable for the aforementioned technical problems. The proposition of algorithms for calculating the accumulation of fatigue damage in non-proportional and multiaxial stresses (especially in terms of the application of rainflow analysis by decomposition of the equivalent stress, as determined by the appropriate “fatigue” criterion) is very important in such computational processes. The entire computational process was implemented in MATLAB with the “Discret_Opt_Fat” main control program. The article presents the theoretical basis for the presented complex problem solution, its algorithmization and the technical application.